Quantitative indicators of microcirculation of the skin of the lower extremities - V. I. Rusin; P. O. Boldizhar; F. V. Gorlenko; M. M. Lopit (Сучасні медичні технології)
Purpose of the study. To study the quantitative indicators of microcirculation and perfusion of the skin of the lower extremities, taking into account the angiosomal theory.